Pengembangan Aplikasi RAM Cleaner Berbasis C++untuk Optimasi Penggunaan Memori Sistem Operasi Windows - Said, Nasruddin; Aziz, Aulia Syarif (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2026)
This research aims to design and develop a C++-based RAM Cleaner application capable of optimizing memory usage by clearing unused memory allocations from running processes. The method used in this study is Experimental and Research and Development (R&D), involving testing on three types of laptops with different specifications. The main issue addressed in this research is how the design and development of a RAM Cleaner application can provide a tangible impact on memory savings and system performance improvement. This is based on the fact that many background processes in the Windows operating system use memory inefficiently, which can lead to system slowdowns and unresponsiveness. With the increasing use of electronic devices, efficient memory management is becoming more important to maintain optimal system performance. Test results show that the RAM Cleaner application can reduce memory usage by between 20% and 30%, depending on the number of running processes. Usage on a Lenovo (8OE1) laptop showed an efficiency of 13%, Acer Aspire 5 A514-51KG-34 reached 24%, and HP Victus 15-Fb achieved 6%.These findings indicate that the C++-based RAM Cleaner application is effective in improving memory usage efficiency and provides a significant contribution to better memory management on the Windows operating system.